Climate variability and malaria trends among children under five in the department of Daloa, Ivory Coast - KROUBA, Débora Isabelle (Geografares, 2025)
This article examined the relationship between malaria and climate. The underlying objective was to address the problem of high malaria prevalence among children under five in Daloa. The Nicholson index method was used to characterize interannual variations in climate parameters. Pearson’s matrix was applied to assess the correlation between climate and malaria. Fluctuations in climate parameters were recorded between 1981 and 2021. The correlation test differed from one parameter to another. These parameters were: rainfall (r=0.66), temperature (r=0.18), and relative humidity (r=0.26). The correlation test concluded that all climate parameters influence malaria morbidity. However, rainfall is the climate factor that most influences malaria prevalence. This situation calls for the adoption of appropriate measures to address it.
Keywords: climate parameters; malaria; Daloa; Ivory Coast